1998
DOI: 10.1046/j.1365-2745.1998.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Can comparative approaches based on plant ecophysiological traits predict the nature of biotic interactions and individual plant species effects in ecosystems?

Abstract: Summary 0The development of general principles regarding biotic interactions involving plants\ or plant species e}ects in ecosystems\ is best achieved through simultaneous evaluation of several species[ We utilized a comparative approach involving 19 dicotyledonous herbaceous species\ to explore possible relationships between several plant eco! physiological traits and plant litter decomposition\ interactions involving competition and herbivory\ and plant species e}ects on soil properties[ 1 Decomposition rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
2
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(215 citation statements)
references
References 63 publications
10
194
2
4
Order By: Relevance
“…Using mixtures of 14 calcareous grassland plant species drawn from three functional groups (nonleguminous forbs, grasses, and leguminous forbs), Hanley et al (2004) concluded that because of the idiosyncratic responses of individual species, the categorization of plants into broad functional groups was of limited use to understand the impacts of elevated atmospheric CO 2 on plant communities. Moreover, plant species which were selected from the dicotyledonous herbs functional group had large difference between species for all of the ecophysiological traits measured (Wardle et al 1998). In this paper, we also found significant differences in ecophysiological traits between grasses.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Using mixtures of 14 calcareous grassland plant species drawn from three functional groups (nonleguminous forbs, grasses, and leguminous forbs), Hanley et al (2004) concluded that because of the idiosyncratic responses of individual species, the categorization of plants into broad functional groups was of limited use to understand the impacts of elevated atmospheric CO 2 on plant communities. Moreover, plant species which were selected from the dicotyledonous herbs functional group had large difference between species for all of the ecophysiological traits measured (Wardle et al 1998). In this paper, we also found significant differences in ecophysiological traits between grasses.…”
Section: Discussionsupporting
confidence: 59%
“…However, in the early successional stage, living environments are difficult for plants to survive due to excessive light, lack of water, and scarce nutrient in the soil (García-Orth & Martínz-Ramos 2011). But the vast energy fixing by plants through strong photosynthetic capacity (Navas et al 2010), root growth (Maestre et al 2001(Maestre et al , 2009, and litter decomposition (Wardle et al 1998;Maestre et al 2001) improves the habitat and accelerates the process of plant succession to a certain extent. Grasses can ameliorate the abiotic environment and facilitate the introduction of other species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation was particularly strong in the 17 graminoid monocots (r l 0.69, P 0.01). In addition, Wardle et al (1998) reported consistent positive (although non-significant) trends between leaf palatability to the beetle Listronotus bonariensis or the slug Deroceras reticulatum and litter decomposition rate in 20 herbaceous dicots in New Zealand. A recurrent pattern emerging from these experiments (Grime et al, 1996 ;Wardle et al, 1998 ; N. Pe!…”
Section: Leaf Structure and Defence As Controllers Of Litter Decomposmentioning
confidence: 90%
“…For instance, ecophysiological approaches, even when not labeled as functional ecology, have been successfully used in studies on species distribution (Borchert 1994), functional convergence (Grime 1977;Wright et al 2002), species interactions (Wardle et al 1998), mechanism of coexistence (Markesteijn et al 2011), environmental filtering (Grime 1977;Borchert 1994), ecosystem processes/services (Wardle et al 1998) and conservation biology (Wikelski & Cooke 2006). …”
Section: What Is Ecophysiology?mentioning
confidence: 99%